2018
DOI: 10.1177/1356336x18755087
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Cognitive and Metacognitive Learning Strategies Scales among preservice physical education teachers: A bifactor analysis

Abstract: Although widely used to measure self-regulated learning strategies, the Motivated Strategies for Learning Questionnaire has not yielded satisfactory construct validity across empirical studies. This study examined its psychometric properties by focusing on one of its subscales, the Cognitive and Metacognitive Learning Strategies Scales, among 419 preservice physical education teachers ( M age = 23.05 years, SD = 4.28) from five physical education teacher preparation programmes in the southwestern United States… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
1
12
0
4
Order By: Relevance
“…The present study is the follow-up to our previous study (Liu et al, 2018b). In the previous study, the MSLQ was modified, validated, and titled the CPSS questionnaire.…”
Section: The Present Studymentioning
confidence: 70%
See 2 more Smart Citations
“…The present study is the follow-up to our previous study (Liu et al, 2018b). In the previous study, the MSLQ was modified, validated, and titled the CPSS questionnaire.…”
Section: The Present Studymentioning
confidence: 70%
“…The 18-item CPSS (Liu et al, 2018b) was used to assess participants’ SRL strategies use. According to the specifications of bifactor modeling (see Holzinger and Swineford, 1937), all 18 items in the CPSS assess cognitive and metacognitive strategies simultaneously under the general factor—General Cognitive Strategies (GCS; see Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were similar to previous studies, although in isolation. In this sense, different studies showed that metacognitive strategies have been positively related to healthy habits such as physical activity practice (Theodosiou et al, 2008;Liu et al, 2019;Coimbra et al, 2021), similarly, previous studies showed how critical thinking has been positively related to habits related to physical activity practice (Pill and SueSee, 2017). However, engagement in learning has not been found to be related to healthy lifestyle habits, although there are studies that have shown a positive relationship between commitment and motivation toward classes with respect to physical activity and healthy diet (Ulstad et al, 2016;Hastie et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Sáez-Delgado, Cofré, Estrada, Fornerod, García, Muñoz & Segovia. Escala de autoeficacia docente para la promoción de la autorregulación del aprendizaje.Julio -Diciembre de 2020http://dx.doi.org/10.33210/ca.v9i3.332Estudios anteriores de escalas diseñadas a nivel de autoeficacia en estudiantes, han explicado mejor la estructura factorial en el diseño de instrumentos usando este tipo de análisis[24],[38]. La explicación de esto se debe a que se trata de medir un constructo complejo y multidimensional.…”
unclassified